Rare giant ovarian metastasis arising from a small primary lung adenocarcinoma: a case report - Wang, Baofeng; Jia, Youjuan; Wang, Jiang; Zhang, Zhenjiang; Ding, Yilin; Lu, Hengxiao (Frontiers in Surgery, 2023)
This intricate case report details an exceptionally rare incidence of ovarian metastasis originating from a primary lung adenocarcinoma (LUAD). The relative rarity of this metastatic pathway in medical literature indicates significant diagnostic challenges.This patient was initially found to have both the ovarian tumor and lung nodule and they were originally considered independent primary tumors, derived from radiological interpretations and biomarker profiling. Nevertheless, subsequent postoperative histopathological and immunohistochemical staining evaluations identified ovarian tumors as invasive adenocarcinoma metastasized from lung. The lung and ovary tumor both showed marked anaplastic lymphoma kinase gene (ALK) protein expression by immunohistochemistry. The molecular pathologic genetic testing for lung tumor also revealed ALK rearrangement positive. The complexity of this case underscores the essentiality of maintaining a high degree of diagnostic vigilance, particularly when confronting synchronous tumors. In addition, immunohistochemical staining plays an important role in diagnosing the ovarian neoplasm's metastatic nature and determining the primary site of metastatic adenocarcinoma. For lung cancer with ovary metastasis patients, the adopting an adaptable treatment approach responsive to evolving diagnostic evidence can improve the accuracy of diagnosis and avoid excessive treatment of patients.